(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the conceptual foundations of multiculturalism and intercultural communication within contemporary educational environments. Drawing on scholarship in political philosophy, applied linguistics, and educational theory, the study explores how cultural diversity manifests in classroom settings and how pedagogical practices must evolve to accommodate it. The article defines multiculturalism as both a descriptive reality the coexistence of multiple cultural groups and a normative political philosophy that seeks the inclusion of historically marginalised communities. Intercultural communication is distinguished from multicultural communication by its emphasis on productive cross-cultural interaction rather than mere coexistence. The article surveys the principal criticisms of multiculturalism, including concerns about social cohesion, the dilution of individual rights, and the risk of reinforcing dominant power structures. It concludes that the future of equitable education depends on equipping both educators and students with the competencies to navigate cultural difference effectively and to build genuinely inclusive learning spaces.